A sexual network approach to sperm competition in a species with alternative mating tactics. (26th September 2014) - Muniz, Danilo G.; Guimarães, Paulo R.; Buzatto, Bruno A.; Machado, Glauco
Lay summary: Mating patterns of animal populations can be described as a sexual network, and this approach may provide insights on sperm competition. Studying an arachnid with alternative mating tactics, we showed that sperm competition is higher among males that sneak copulations. Moreover, aggregated harems are hotspots of sneaker invasions, suggesting that the spatial structure of harems has strong influence on the topology of the sexual network. Abstract : Alternative mating tactics are common among species exhibiting resource defense polygyny. While large territorial males aggressively defend harems, small sneaker males generally invade these harems to mate furtively. The result is a sexual network that provides information on the sperm competition intensity (SCI) faced by males of both morphs. Here, we use metrics derived from the network approach to compare SCI between sneakers and territorials of the male-dimorphic harvestman Serracutisoma proximum . We also tested hypotheses about the influence of harem size and spatial distribution of harems on the SCI faced by territorial males. Sneakers faced, on average, higher levels of SCI than territorials, while the SCI faced by territorials was more variable than that of sneakers. Owners of large harems faced less intense sperm competition than owners of small harems, suggesting that sperm competition is more diluted among females in large harems. At the population level, sneakers concentrated their invasions on neighboring harems that were spatially aggregated. We argue that the spatial distribution of harems is an important element influencing the topology of the sexual network, and that the spatially explicit approach we used here can bring new insights to the study of sperm competition and mating systems in a wide range of organisms.